2020
DOI: 10.1177/1120672120980951
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography biomarkers for visual acuity in patients with idiopathic epiretinal membrane

Abstract: Purpose: To investigate the correlation between outer and inner retina optical coherence tomography (OCT) biomarkers and visual acuity in patients with idiopathic epiretinal membrane (iERM) and identify which of them may be predictive of visual function. Methods: A retrospective cross-sectional single-center study was conducted that included patients diagnosed with iERM. Spectral domain OCT images were obtained and assessed qualitatively and quantitatively. The association of OCT parameters with best corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
13
0
2
Order By: Relevance
“…We have found DRIL and CMT to be significant predictors for final BCVA in a multiple regression analysis. This outcome is comparable with the results of Karasavvidou et al 23 , who found severe DRIL and maximal retinal thickness to be significant predictors. Nevertheless, intra- and interobserver reliability in diagnosing OCT biomarkers for success in visual acuity among patients with iERM are different between biomarkers, indicating potential for disagreement in diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have found DRIL and CMT to be significant predictors for final BCVA in a multiple regression analysis. This outcome is comparable with the results of Karasavvidou et al 23 , who found severe DRIL and maximal retinal thickness to be significant predictors. Nevertheless, intra- and interobserver reliability in diagnosing OCT biomarkers for success in visual acuity among patients with iERM are different between biomarkers, indicating potential for disagreement in diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Wir fanden in der multiplen Regressionsanalyse DRIL und CMT als signifikante Prädiktoren für den postoperativen BCVA. Dieses Ergebnis ist vergleichbar mit den Resultaten von Karasavvidou et al [23], die berichteten, dass ausgeprägte DRIL und hohe retinale Dicke signifikante Prädiktoren sind. Unabhängig von diesen Resultaten zeigen die Intra-und Interobserver-Reliabilitätswerte für die Diagnose von OCT-Biomarkern für postoperativen Visuserfolg bei Patientinnen und Patienten mit iERM Unterschiede zwischen den einzelnen Biomarkern und weisen ein Potenzial für deren unterschiedliche Bewertung in der Diagnose auf.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…However, previous studies regarding the correlation between visual acuity and retinal structural changes on OCT have reported conflicting results. Some studies have suggested that outer retinal change is a determinant of visual function,8–10 while others have addressed the role of inner retinal changes 11–16. Meanwhile, some OCT-based ERM classifications have been proposed to correlate with visual function,1,11,17,18 but none have been widely accepted in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that outer retinal change is a determinant of visual function, [8][9][10] while others have addressed the role of inner retinal changes. [11][12][13][14][15][16] Meanwhile, some OCT-based ERM classifications have been proposed to correlate with visual function, 1,11,17,18 but none have been widely accepted in clinical practice. In other words, the OCT biomarkers for visual impairment in patients with ERM are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%